CONTEXTUALIZATION OF BLOODSHED IN OTHELLO AND TITUS ANDRONICUS WITH AN ETHNIC HINDSIGHT VIEW - SOEDE, Casimir Comlan; KLOUTSE, Kodjo Biava; AKONDO, Dyfaizi Nouhr-Dine (My University, 2020)
Abstract The diversities in languages, origins and differences in skin-colour seem to be the source of many socio-ethnic conflicts on the planet. In that vein, the concept of ethnicity reads as the safeguarding of group unity or interest and thus implies a maintaining of a tradition of secrecies and group supremacy over other ethnic groups. This appears to hinder the smooth progress that needs to be revisited in most human communities. Through the formalist lens, the present article contends that a re-reading coupled with a redefinition of the “I” and “we” becomes peremptory with individual persons and groups in order to lay the foundations of a harmonious world. Résumé La diversité de provenance, de langues, et les différences de la couleur de peau semblent être la source de nombreux conflits socio-ethniques dans le monde. De ce fait, le concept de l’ethnicité se lit comme la sauvegarde de l’unicité ou l’intérêt du groupe et implique le maintien de valeurs codées et une suprématie de groupe sur d’autres groupes ethniques. Cette situation constitue un frein au progrès harmonieux de l’humanité qui reste à repenser. Dans une démarche formaliste, le présent article soutient qu’à travers la mise en scène des personnages dans Othello et Titus Andronicus, une relecture couplée d’une redéfinition du ‘je’ et du ‘nous’ s’avère péremptoire autant au niveau de l’individu que du groupe en vue de mettre les bases d’un monde harmonieux.
Keywords: Keywords: Ethnicity; Unity; Secret; Supremacy; Dominance; Mots clés : l’ethnicité; l’unité; le secret; la suprématie; la dominance